2017
DOI: 10.3906/biy-1702-48
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and amplification of ancient DNA from Herculaneum victims killed by the 79 AD Vesuvius hot surges

Abstract: In thermally damaged archaeological bones the quantity, quality, and amplifiability of DNA are very much reliant on both the extent of heating and the environmental conditions of the burial context. In this study we tested the possibility of extracting and amplifying ancient DNA from human bone remains of Herculaneum victims of the 79 AD eruption of Vesuvius using a combination of histochemical and molecular methods. Long bone samples with variable degrees of chromatic and morphological alterations consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…At Herculaneum, instead, after the rapid vanishing of soft tissue by ≥ 500 °C exposure 22 , the permanently waterlogged ash bed in which the skeleton was buried must have inhibited the microbial chemical modifications, allowing the long-term survival of organic matter. Such a type of environmental context seems to explain the reason of the highlighted good preservation of proteins, as well as the survival of collagen and DNA 24 , 87 .…”
Section: Discussionmentioning
confidence: 99%
“…At Herculaneum, instead, after the rapid vanishing of soft tissue by ≥ 500 °C exposure 22 , the permanently waterlogged ash bed in which the skeleton was buried must have inhibited the microbial chemical modifications, allowing the long-term survival of organic matter. Such a type of environmental context seems to explain the reason of the highlighted good preservation of proteins, as well as the survival of collagen and DNA 24 , 87 .…”
Section: Discussionmentioning
confidence: 99%
“…6 These authors contributed equally: Olga Rickards and Fabio Macciardi. * email: gabrielescor@gmail.com; pierfrancesco.fabbri@unisalento.it; fmacciar@uci.edu Past studies have shown the possibility of retrieving genetic data from both human and zooarchaeological remains in Pompeii [6][7][8][9][10][11][12] , but those initial analyses were limited to short stretches of mitochondrial DNA obtained using PCR-based methods. New available methodologies, based on high-throughput shotgun sequencing, DNA capture, enrichment strategy 13,14 , as well as using optimal sources of ancient DNA (aDNA) from teeth and petrous bones 15,16 , have dramatically increased the amount of data that can be obtained from previously unsuitable samples for genetic research, and may open new avenues to substantially increase the knowledge of the genetic diversity in the ancient Pompeian population.…”
Section: Openmentioning
confidence: 99%